Representation of language functions in the bilingual brain - Mildner, Vesna (2000)
Representation of language functions in the human brain has been a subject of much research in neuroscience, psychology and linguistics. Behavioral and sophisticated instrumental techniques have shown time and again that the brain is anatomically and even more so functionally asymmetrical; that it possesses a high degree of plasticity which enables it to learn from experience and recover from lesions even until later in life than originally thought; and that there is no clear on-eo-one correspondence between structure and function.
Within the body of neurolinguistic research studz of the bilinguals has occupied an important place. With respect to neurolinguistic organization of bilinguals three hypotheses have emerged: (1) left hemisphere is dominant for both languages, (2) left-lateralization is not as clear in bilinguals as in monolinguals, and (3) two languages are lateralized to the opposite hemispheres.
The paper will address major neurolinguistic issues in terms of bilingual functioning, including a review of neuroimaging and behavioral data, differencital recoverz from aphasia data and recent experimental results.
Projekt MZOS
ENG